Aberrant tetranectin expression in human breast carcinomas as a predictor of survival. Issue 4 (26th March 2004) - Obrist, P; Spizzo, G; Ensinger, C; Fong, D; Brunhuber, T; Schäfer, G; Varga, M; Margreiter, R; Amberger, A; Gastl, G; Christiansen, M
Abstract : Aims: Tetranectin (TN), a plasminogen kringle 4 binding protein, is thought to play a prominent role in the regulation of proteolytic processes via binding to plasminogen. The aim of this study was to evaluate the expression of TN in human breast cancer and adjacent normal breast tissue and to determine the impact of this expression on survival. Methods: A retrospective analysis was performed on 189 patients with breast cancer, with a median follow up time of 10.6 years. The expression of TN was assessed in tumour tissue and adjacent normal breast tissue by immunohistochemistry, and the prognostic relevance of its expression in tumour cells was evaluated. Results: TN was highly expressed in connective tissue fibres surrounding normal breast epithelium, but not in normal epithelial cells. High expression of TN in tumour cells was found in 131 (69%) of the tumour samples. By western blot analysis, no significant difference in the amount and molecular weight of TN was seen between tumour tissue and normal tissue. Strong TN immunoreactivity in tumour tissue was predictive of poor disease free and tumour specific overall survival. By multivariate analysis, high TN expression in cancer cells was an independent prognostic factor for disease free and tumour specific overall survival. Conclusions: Our results demonstrate differential TN expression in normal and malignant breast tissue and a prognostic impact of TN protein expression in breast carcinoma tissue. These data suggest a possible role of TN in invasiveness and the metastatic spread of human breast cancer.